New Mediterranean Biodiversity Records (October, 2014) - S. KATSANEVAKIS; Ü. ACAR; I. AMMAR; B. A. BALCI; P. BEKAS; M. BELMONTE; C. C. CHINTIROGLOU; P. CONSOLI; M. DIMIZA; K. FRYGANIOTIS; V. GEROVASILEIOU; V. GNISCI; et al. (Mediterranean Marine Science, 2014)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of alien and native species respectively. The new records of alien species include: the red alga Asparagopsis taxiformis (Crete and Lakonicos Gulf) (Greece); the red alga Grateloupia turuturu (along the Israeli Mediterranean shore); the mantis shrimp Clorida albolitura (Gulf of Antalya, Turkey); the mud crab Dyspanopeus sayi (Mar Piccolo of Taranto, Ionian Sea); the blue crab Callinectes sapidus (Chios Island, Greece); the isopod Paracerceis sculpta (northern Aegean Sea, Greece); the sea urchin Diadema setosum (Gökova Bay, Turkey); the molluscs Smaragdia souverbiana, Murex forskoehlii, Fusinus verrucosus, Circenita callipyga, and Aplysia dactylomela (Syria); the cephalaspidean mollusc Haminoea cyanomarginata (Baia di Puolo, Massa Lubrense, Campania, southern Italy); the topmouth gudgeon Pseudorasbora parva (Civitavecchia, Tyrrhenian Sea); the fangtooth moray Enchelycore anatine (Plemmirio marine reserve, Sicily); the silver-cheeked toadfish Lagocephalus sceleratus (Saros Bay, Turkey; and Ibiza channel, Spain); the Indo-Pacific ascidian Herdmania momusin Kastelorizo Island (Greece); and the foraminiferal Clavulina multicam erata (Saronikos Gulf, Greece). The record of L. sceleratus in Spain consists the deepest (350-400m depth) record of the species in the Mediterranean Sea. The new records of native species include: first record of the ctenophore Cestum veneris in Turkish marine waters; the presence of Holothuria tubulosa and Holothuria polii in the Bay of Igoumenitsa (Greece); the first recorded sighting of the bull ray Pteromylaeus bovinus in Maltese waters; and a new record of the fish Lobotes surinamensis from Maliakos Gulf.